Multi-scale assessment of environmental changes impact on subarctic glacierized watersheds hydrology - Chesnokova, Anna (École de technologie supérieure, 2020)
Subarctic glacierized catchments are complex hydrological systems of paramount importance not only for water resources management but also for various ecosystem services. They are environmentally fragile and exert a high sensitivity to changes in climatic forcing. Several studies indicated the hydrological importance of the non-glacierized portions of these watersheds by illustrating the potential water storage capacity and runoff production of their proglacial areas. However, on a watershed scale, the hydrological role of every single component other than glaciers is not yet well understood. I hypothesized that subarctic proglacial areas play an important role in the glacierized watersheds hydrology and that glacier retreat does not entirely define their hydrological response to climate change. Hence, to accurately project the response of subarctic glacierized catchments to environmental changes, it is necessary to better understand and quantify the contribution of each hydrological component in runoff production. The primary objective of this project is thus to improve the knowledge necessary to project the impact of environmental changes on the hydrology of subarctic regions by (i) isolating and quantifying the role of shrinking glaciers in recent hydrological changes in the southwestern Yukon as well as estimating future hydrological changes in the region, (ii) disentangling the importance of various hydrological components to the total summer runoff in the headwaters of a subarctic glacierized watershed, and (iii) analyzing the genesis of icings to obtain new insights into the generation of winter baseflow and winter hydrological processes in the headwaters of subarctic glacierized watersheds of different complexity. To achieve these objectives, three summer field campaigns in a glacierized watershed of the St. Elias Mountains, Yukon, Canada, were conducted. The data collected were complemented with laboratory activities, statistical analyses, and remote sensing. Due to the high hydrological complexity met ...